Designing a Rational Follow-Up Schedule for Patients with Extremity Soft Tissue Sarcoma - Wilson, David A. J.; Gazendam, Aaron; Visgauss, Julia; Perrin, David; Griffin, Anthony M.; Chung, Peter W.; Catton, Charles N.; Shultz, David; Ferguson, Peter C.; Wunder, Jay S. (Annals of surgical oncology, 2020)
Purpose The risk of tumor recurrence after resection of soft tissue sarcoma (STS) necessitates surveillance in follow-up. The objective of this study was to determine the frequency/timing of metastasis and local recurrence following treatment for soft tissue sarcoma, and to use these data to justify an evidence-based follow-up schedule. Methods Utilizing a prospective database, a retrospective single center review was performed of all patients with minimum 2-year follow-up after resection of a localized extremity STS. Kaplan–Meier estimates were used to calculate the incidence of local recurrence and metastases on an annual basis for 10 years. Results We identified a total of 230 low-grade, 626 intermediate-grade and 940 high-grade extremity STS and a total of 721 events, 150 local recurrences and 571 metastases. Based on tumor size and grade, follow-up cohorts were developed that had similar metastatic risk. Using pre-determined thresholds for metastatic event, a follow-up schedule was established for each cohort. Conclusion Based on our results we recommend that patients with small low-grade tumors undergo annual follow-up for 5 years following definitive local treatment. Patients with large low-grade tumors, small intermediate-grade and small high-grade tumors should have follow-up every 6 months for the first 2 years, then yearly to 10 years. Only patients with large intermediate- or high-grade tumors require follow-up every 3 months for the first 2 years, then every 6 months for years 3–5, followed by annually until 10 years.